Cemento-Ossifying Fibroma in a Patient with End-Stage Renal Disease - Divya Gopinath; V. T. Beena; G. Sugirtharaj; K. Vidhyadharan; K. Salmanul Faris; Sajai J. Kumar (Hindawi Limited, 2013)
The presence of chronic renal disease (CRD) is a predisposing factor for the occurrence of soft and hard tissue lesions in the oral cavity. The cemento-ossifying fibroma (COF) is an uncommon benign fibroosseous lesion composed of fibrocellular component and calcified materials like cementum and woven bone. A 37-year-old female patient undergoing chronic haemodialysis reported to our institution with a complaint of slow growing, nontender swelling of mandible of 6-month duration. Computed tomography disclosed an ill-defined lesion showing thinning and expansion of buccal as well as lingual cortical plate with flecks of radiopacity in centre. Incision biopsy revealed histological characteristics consistent with cemento-ossifying fibroma. The lesion was excised under local anesthesia. The histopathological examination revealed irregularly shaped bone and cementum-like hard tissue calcifications contained within hypercellular fibrous tissue stroma, leading to a confirmation of the diagnosis of cemento-ossifying fibroma. This paper aims to provide light to the fact that the soft and hard tissues of the oral region may become susceptible to the development of pathological growths in case of some particular systemic conditions.